Pengaruh CR dan DER Terhadap NPM pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di BEI Periode 2019-2023 - Muhamad Rijal Pamungkas; Siti Mufidatun Nafisah (Indo Publishing, 2025)
This study aims to analyze the effect of Current Ratio and Debt to Equity Ratio on Net Profit Margin in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period. This research is a quantitative study using secondary data. The population in this study consisted of 84 manufacturing companies in the food and beverage sub-sector listed on the IDX. The number of samples used in this study were 60 company annual financial reports. Samples were selected using purposive sampling method. The data analysis techniques used are panel data regression analysis test, classical assumption test, and hypothesis testing. Data processing in this study using STATA. The results showed that partially Current Ratio (CR) has a positive and significant effect on Net Profit Margin (NPM). Partially DER has a negative and significant effect on Net Profit Margin (NPM). Simultaneously based on the F test, Current Ratio (CR) and Debt to Equity Ratio (DER) have a significant effect on Net Profit Margin (NPM). The calculation of the coefficient of determination shows that the variables Current Ratio (CR) and Debt to Equity Ratio (DER) on Debt to Equity Ratio (NPM) have an influence of 27.21% and the remaining 72.21% is influenced by other variables outside this study.